Plasma-Derived Exosome MiR-19b Acts as a Diagnostic Marker for Pancreatic Cancer - Wang, Lei; Wu, Jinxiang; Ye, Naikuan; Li, Feng; Zhan, Hanxiang; Chen, Shihong; Xu, Jianwei (Frontiers in Oncology, 2021)
Background Diagnosis of pancreatic cancer (Pca) is challenging. This study investigated the value of plasma-derived exosome miR-19b (Exo-miR-19b) in diagnosing patients with Pca. Methods Plasma was collected from 62 patients with Pca, 30 patients with other pancreatic tumor (OPT), 23 patients with chronic pancreatitis (CP), and 53 healthy volunteers. MiR-19b levels in plasma-derived exosomes were detected. Results Plasma-derived Exo-miR-19b levels normalized using miR-1228 were significantly lower in Pca patients than in patients with OPT, CP patients, and healthy volunteers. The diagnostic values of Exo-miR-19b normalized using miR-1228 were superior to those of serum cancer antigen 19-9 (CA19-9) in differentiating Pca patients from healthy volunteers (area under the curve (AUC): 0.942 vs. 0.813, p = 0.0054), potentially better than those of CA19-9 in differentiating Pca patients from CP patients (AUC: 0.898 vs. 0.792, p = 0.0720), and equivalent to those of CA19-9 in differentiating Pca patients from patients with OPT (AUC: 0.810 vs. 0.793, p = 0.8206). When normalized using Caenorhabditis elegans miR-39 (cel-miR-39), Exo-miR-19b levels in Pca patients were significantly higher than those in patients with OPT, CP patients, and healthy volunteers. The diagnostic values of Exo-miR-19b normalized using cel-miR-39 were equivalent to those of CA19-9 in differentiating Pca patients from healthy volunteers (AUC: 0.781 vs. 0.813, p = 0.6118) and CP patients (AUC: 0.672 vs. 0.792, p = 0.1235), while they were inferior to those of CA19-9 in differentiating Pca patients from patients with OPT (AUC: 0.631 vs. 0.793, p = 0.0353). Conclusion Plasma-derived Exo-miR-19b is a promising diagnostic marker for Pca. The diagnostic value of plasma-derived Exo-miR-19b normalized using miR-1228 is superior to that of serum CA19-9 in differentiating patients with Pca from healthy volunteers.